1996
DOI: 10.1007/bf00020480
|View full text |Cite
|
Sign up to set email alerts
|

Changes in abundance of an abscisic acid-responsive, early cysteine-labeled metallothionein transcript during pollen embryogenesis in bread wheat (Triticum aestivum)

Abstract: A clone for an embryoid-abundant, early cysteine-labeled metallothionein (EcMt) gene has been isolated from a wheat pollen embryoid cDNA library. The transcript of this gene was only expressed in embryogenic microspores, pollen embryoids, and developing zygotic embryos of wheat. Accumulation of the EcMt mRNA showed a direct and positive correlation with an increase of the plant hormone, abscisic acid (ABA) in developing pollen embryoids. Treating cultures with an inhibitor of ABA biosynthesis, fluridone, suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 26 publications
1
44
0
3
Order By: Relevance
“…Type 3 MTs are expressed abundantly in the ripe fruits (Clendennen & May, 1997;Ledger & Gardner, 1994;Reid & Ross, 1997), and expression of Type 4 MTs, also known as the Ec type, was only found in developing seeds so far (Chyan et al, 2005;Lane et al, 1987). A vast number of stimuli have been demonstrated capable of inducing MT genes expression in plants, including natural senescence (Bhalerao et al, 2003), hormones like ABA (Reynolds & Crawford, 1996), ethylene (Coupe et al, 1995), wounding and virus infection (Choi et al, 1996), heat shock (Hsieh et al, 1995), sucrose starvation (Hsieh et al, 1996), UV-light (Foley & Singh, 1994), cold and salt stress (Reid & Ross, 1997), etc. Apparently, different types of MTs respond to different factors, which is especially true when treated with heavy metal stress under different concentrations.…”
Section: Metallothionein: Metal-binding Protein and Morementioning
confidence: 99%
See 1 more Smart Citation
“…Type 3 MTs are expressed abundantly in the ripe fruits (Clendennen & May, 1997;Ledger & Gardner, 1994;Reid & Ross, 1997), and expression of Type 4 MTs, also known as the Ec type, was only found in developing seeds so far (Chyan et al, 2005;Lane et al, 1987). A vast number of stimuli have been demonstrated capable of inducing MT genes expression in plants, including natural senescence (Bhalerao et al, 2003), hormones like ABA (Reynolds & Crawford, 1996), ethylene (Coupe et al, 1995), wounding and virus infection (Choi et al, 1996), heat shock (Hsieh et al, 1995), sucrose starvation (Hsieh et al, 1996), UV-light (Foley & Singh, 1994), cold and salt stress (Reid & Ross, 1997), etc. Apparently, different types of MTs respond to different factors, which is especially true when treated with heavy metal stress under different concentrations.…”
Section: Metallothionein: Metal-binding Protein and Morementioning
confidence: 99%
“…The wheat type 4 MT Ec gene was specially expressed during pollen embryogenesis, and its accumulation correlates well with increase of the plant hormone abscisic acid (ABA). It's suggested that induced by the ABA signal, this zinc-containing Ec may regulate certain gene expression via zinc trafficking with zinc-dependent DNA/RNA polymerase or zinc-finger proteins (Reynolds & Crawford, 1996). MTs have been implicated during senescence in many plants (Bhalerao et al, 2003;Breeze et al, 2004;Buchanan-Wollaston & Morris, 2000), and hypotheses for MT's role in senescence primarily reckon on either MTs' chelating and detoxifying abilities which alleviate the senescence-induced metal ion disturbance and oxidative burst, or the release of necessary metal ions to required places for nutrient recycling.…”
Section: Metallothionein: Metal-binding Protein and Morementioning
confidence: 99%
“…In vitro embryo cultures derived from both somatic and gametophytic tissues have been used successfully as tools to identify genes expressed during early embryo development (Wilde et al, 1988;Aleith and Richter, 1990;Reynolds and Kitto, 1992;Wurtele et al, 1993;Boutilier et al, 1994;Zarsky et al, 1995;Reynolds and Crawford, 1996;Schmidt et al, 1997;Vrinten et al, 1999). One of these genes, SO-MATIC EMBRYOGENESIS RECEPTOR KINASE , was recently shown to enhance Arabidopsis somatic embryo development (Hecht et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Differentially expressed genes isolated from barley microspore cultures include nonspecific lipid transfer protein (ECLTP), glutathione S-transferase (ECGST), an unknown protein (ECA1), and 14-3-3 isoforms (Vrinten et al, 1999;Maraschin et al, 2003). A Cys-labeled metallothionein protein expressed from 6 h after embryo induction was identified in wheat microspore cultures (Reynolds and Crawford, 1996;Reynolds, 1997). Using mRNA differential display, a small secreted protein (CLE19) expressed at the globular to heart stage (10 d) of B. napus MDEs was isolated (Fiers et al, 2004).…”
mentioning
confidence: 99%